2006
DOI: 10.1158/1078-0432.ccr-05-2020
|View full text |Cite
|
Sign up to set email alerts
|

The Uracil Breath Test in the Assessment of Dihydropyrimidine Dehydrogenase Activity: Pharmacokinetic Relationship between Expired 13CO2 and Plasma [2-13C]Dihydrouracil

Abstract: Purpose: Dihydropyrimidine dehydrogenase (DPD) deficiency is critical in the predisposition to 5-fluorouracil dose-related toxicity. We recently characterized the phenotypic [2-13 C]uracil breath test (UraBT) with 96% specificity and 100% sensitivity for identification of DPD deficiency. In the present study, we characterize the relationships among UraBT-associated breath C]uracil concentrations were determined over 180 minutes using IR spectroscopy and liquid chromatography-tandem mass spectrometry, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 21 publications
1
56
0
Order By: Relevance
“…More recently, we validated the UraBT by evaluating plasma [2-13 C]uracil, [2-13 C]dihydrouracil, and breath 13 CO 2 pharmacokinetics in subjects with normal DPD enzyme activity as well as DPD deficiency. We showed that UraBT 13 CO 2 concentrations are significantly correlated with DPD enzyme activity and plasma [2-13 C]uracil clearance and [2-13 C]dihydrouracil formation (19). These results suggest that the UraBT may be used to rapidly assess variability in in vivo pyrimidine catabolism.…”
Section: -Fluorouracilmentioning
confidence: 70%
See 2 more Smart Citations
“…More recently, we validated the UraBT by evaluating plasma [2-13 C]uracil, [2-13 C]dihydrouracil, and breath 13 CO 2 pharmacokinetics in subjects with normal DPD enzyme activity as well as DPD deficiency. We showed that UraBT 13 CO 2 concentrations are significantly correlated with DPD enzyme activity and plasma [2-13 C]uracil clearance and [2-13 C]dihydrouracil formation (19). These results suggest that the UraBT may be used to rapidly assess variability in in vivo pyrimidine catabolism.…”
Section: -Fluorouracilmentioning
confidence: 70%
“…Recently, we developed and optimized the UraBT to rapidly (<1 hour) screen cancer patients for reduced DPD enzyme activity (18). Subsequently, we did a pharmacokinetic validation of the UraBT by characterizing relationships present among UraBT-associated breath 13 CO 2 metabolite formation, plasma [2-13 C]dihydrouracil formation, plasma [2-13 C]uracil clearance, and PBMC DPD enzyme activity in normal and DPD-deficient subjects (19). More recently, we showed that the UraBT is a rapid method suitable for population studies by screening 13 East Indian subjects for DPD deficiency subsequent to our initial identification and characterization of DPD deficiency in an East Indian cancer patient with severe 5-FU toxicity (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since eighties, the numerous methods based on determination of DPD status were advised to predict serious 5-FU-related toxicity. The function tests have been used for measurement of DPD enzyme activity by 2-[ 13 C]-uracil breath test, or determining uracil/dihydrouracil or [ 14 C]-thymine/dihydrothymine plasma ratio [32][33][34]. Substantial drawbacks of function tests are a need for specialized technology approaches or the use of radiolabeled chemicals not available worldwide [34].…”
Section: Discussionmentioning
confidence: 99%
“…Van Staveren et al [59] showed that a plasma-based uracil screening test can differentiate between patients with deficient or normal DPD activity based on the uracil/dihydrouracil ratio in plasma. Mattison et al [60,61] showed that breath 13 CO2 appearance after administration of 2-13 C-uracil parallels plasma 2-13 C-uracil and 2-13 C-dihydrouracil pharmacokinetics and is an accurate measure of interindividual variation in DPD activity. Currently, none of the approaches is preferred.…”
Section: Assessment Of Patientsmentioning
confidence: 99%